Energy consumption analysis of a typical house in Cyprus - Florides, Georgios A.; Kalogirou, Soteris A.; Tassou, Savvas A. (My University, 2000)
This study uses TRNSYS to estimate the energy consumption of the typical houses of Cyprus. For the calculations, a Typical Meteorological Year for the Nicosia area and a typical model house are used. The internal house temperature, when no air-conditioning is used, is simulated. The effect on the temperature and the heating and cooling loads that various wall and roof constructions have, is determined
Keywords: Cooling; Heating; Computer simulation